Valproate, Learning Disorders, and Epileptiform EEG - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
The effect of sodium valproate (VPA) on learning and behavior problems in 8 children with EEG epileptiform discharges but without clinical seizures was determined in a randomized, bouble-blind, crossover study at Children's Hospital, McMaster University, Hamilton, Ontario, Canada.